Site-specific targeting of psoralen photoadducts with a triple helix-forming oligonucleotide: characterization of psoralen monoadduct and crosslink formation. - Gasparro, F P (1994)
A polypurine tract in the supF gene of bacteriophage lambda (base pairs 167-176) was selected as the target for triple helix formation and targeted mutagenesis by an oligopurine (5'-AGGAAGGGGG-3') containing a chemically linked psoralen derivative (4'-hydroxymethyl-4,5',8-trimethylpsoralen) at its 5' terminus (psoAG10). The thymines at base pairs 166 and 167, a 5'ApT site, were targeted for photomodification. Exposure of the triple helical complex to long wavelength ultraviolet radiation led to the covalent binding of psoAG10 to the targeted region in the supF gene and to the induction of site-specific mutations. We report here experiments to characterize the photomodification of the targeted region of the supF gene in the context of triple helix formation. An electrophoretic mobility-shift assay showed that, at low radiation doses, monoadducts at base pair 166 were the major photoadducts. At higher doses the monoadducts were converted to crosslinks between base pairs 166 and 167. HPLC analysis of enzymatically hydrolyzed photoreaction mixtures was used to confirm the electrophoresis results. A strong strand preference for specific photoadduct formation was also detected.